ANALISIS SENTIMEN KLUB SEPAKBOLA PERSIJA JAKARTA PADA SOSIAL MEDIA TWITTER MENGGUNAKAN ALGORITMA NAÏVE BAYES - Bagas Guseza Antito, (2022)
Social media is a new identity for the Indonesian people at this time, as well as a lifestyle that is difficult to forget. Along with the development of the era, social media is widely spread on the internet, each user is free to use the social media they want, even each user can have more than one social media. One of them is social media Twitter, Twitter is included in social media that can be run on Android and iOS smartphones or also through the website. Twitter users in Indonesia in particular, often share their opinions in various fields, one of which is the field of sports, especially the Persija Jakarta Football Club. We can see various kinds of sentiments towards the Persija Jakarta Football Club through Twitter Social Media. Based on the conditions previously mentioned, a study related to public opinion related to the performance or quality of the Persija Jakarta Football Club is needed. One of the efforts carried out is through a sentimental analysis of the Persija Jakarta Football Club on Twitter Social Media and using the classification method and the Naïve Bayes algorithm to classify tweets that are good or bad given by the community related to the Persija Jakarta Football Club.